Are religious consumers more ethical and less Machiavellian? A segmentation study of Millennials. (25th January 2019) - Arli, Denni; Tkaczynski, Aaron; Anandya, Dudi
Abstract: Millennial consumers are increasingly becoming important actors in business that account for sufficient purchasing power. However, Millennials are infamously narcissistic and their views of ethics are more relaxed than previous generations (i.e., Baby Boomers, Generation X). Millennials remain poorly understood in general, especially in the context of developing countries. Hence, the purpose of this study was to profile this generation by segmenting Millennials in Indonesia and investigating differences between these segments on their ethical beliefs and Machiavellianism, an important personality characteristic. This study used a convenience sample from a university in Indonesia ( N = 540). The TwoStep cluster analysis produced three segments, namely, "The Religious Millennials", "The Lukewarm Religious Millennials" and "The Least Religious Millennials". Consumers who are highly religious are less likely to engage in various unethical behaviours. Interestingly, no significant differences were found between The Lukewarm Millennials and The Least Religious Millennials on their ethical beliefs. This research makes several research contributions. First, this study extended the Hunt–Vitell theory of ethics, where an individual (i.e., Millennials) confronts a problem perceived as having ethical content. Second, the study examined consumer ethics in the context of developing countries where religion plays a significant role in people's daily life. Third, through understanding different segments, the results assist educators, social marketers and public policy makers in creating an effective campaign to reduce unethical behaviour among Millennials.